IMPROVING PROVISION OF PARKINSON'S DISEASE EXERCISE CLASSES. Issue 12 (15th November 2016) - Pujara, Priyanka; Rideout, Jane; Carroll, Camille
Abstract : Background and objectives: Increasing evidence demonstrates the benefits of regular exercise in Parkinson's disease. A patient identified absence of administrative support as a barrier to local exercise class provision and organised a pilot exercise course to overcome this. We aimed to expand this initiative and undertake a comprehensive evaluation of barriers across Devon and Cornwall, recommend further interventions of widespread applicability and assess the impact of exercise classes on patients' exercise habits. Methods: Telephone interviews were conducted with volunteer members from 79% of Parkinson's UK Devon and Cornwall branches. 72% provided exercise classes; 28% did not. The Self-efficacy for Exercise (SEE) scale was administered to participants in the pilot course on entry and repeated on course completion. Additional physical measurements involved Timed up and Go, Single Leg Stance and Sit and Reach tests. Results: Common difficulties for existing classes were transport (100%), class support volunteers (75%), patient motivation (63%) and personal concerns (50%). Inadequate administrative support was the greatest barrier (67%) for localities without classes and also affected existing classes (25%). 8 people with Parkinson's participated in the pilot course: M:F=3:5; median disease duration 7 years (1 to 17); median SEE 59 (25 to 81). SEE scores showed no improvement. All physical tests demonstrated improvement and the Sit and Reach achieved statistical significance. Conclusions: Our data informs the design of targeted local support packages: taxi transport arrangements; student physiotherapists to deliver classes; Parkinson's UK facilitated administrative support; and motivational video encouraging patient participation. Facilitating comprehensive exercise class provision will not only benefit patients, but also provide an infrastructure to evaluate potential benefits of exercise.